If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying d + -8 = -22 Reorder the terms: -8 + d = -22 Solving -8 + d = -22 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + d = -22 + 8 Combine like terms: -8 + 8 = 0 0 + d = -22 + 8 d = -22 + 8 Combine like terms: -22 + 8 = -14 d = -14 Simplifying d = -14
| 9ln(6x)=45 | | 2+x=3x-14 | | ln(x^4)=8 | | 10=12-x | | 4x-1=14-121 | | lnx^4=8 | | -6x+5=-91+2x | | 4x-1=14-21 | | (2-v)(4v+3)=0 | | 4x+34=11-29 | | x^2-(2+2)*2=10 | | 7-7x=7x-91 | | 4x+5=-51+10x | | 3(2-x)-1=4(3-x) | | x(3x-5)(x+4)(x-7)=0 | | -6(6x+5)=-246 | | 4x+5=51-10x | | y=-2(x-4)2nd+3 | | 330*1=-16x | | k^2+6k+8=0 | | 4t-2(3-t)-3(t-7)= | | q^2+2q-48=0 | | 118-4=5x+10 | | Jx+ky=m | | y=-2(x-4)2+3 | | 4.5x-3.4=2.1x-.4 | | 5x^2+40x+35=0 | | -5n(4n-1)=0 | | -6-6x=12-10x | | 4x^2=36x-72 | | 3x+9=10+3x+1 | | X^4-12x^2+35=0 |